Clinic, macroscopic, cytomorphologic and histopathologic features of canine transmissible venereal tumor in two bitches: First report from Kyrgyzstan. Clinical case - Hatipoglu, Fatih; Risvanli, Ali; Kadiraliyeva, Nariste; Zhumagulov, Iskhak (Univ Zulia, Facultad Ciencias Veterinarias, 2025)
Canine transmissible venereal tumour (CTVT) is a spontaneously arising, contagious neoplasm in dogs that propagates via the direct implantation of viable tumour cells between animals. Transmission predominantly occurs during mating, leading to the development of growths chiefly on the external genitalia of both males and females. In this case report, it is aimed to describe the clinical, cytological, macroscopic and histopathological findings of two bitches with CTVT. In the clinical examination of both bitches, an 8-month-old Husky and 2-years-old Alabai crossbred, protruding, irregular, ulcerated and bleeding structures were observed in the vulva. In cytological examinations, round to polyhedral-shaped cells with an eccentrically located nucleus, multiple mitosis and the characteristic distinct, cytoplasmic vacuolations with clear outlines were observed. Histopathological examinations of both cases revealed round or polyhedral neoplastic cells arranged in solid sheets or rows supported by fibrovascular connective tissue septa. Numerous mitotic figures were also observed together with tumor cells. Tumor cells with indistinct cell borders had eosinophilic and finely granular cytoplasmic structures. Necrotic changes in tumor cells and hemorrhage foci were also observed. A tumor cell embolism consisting of tumor cells adherent to the vessel wall was observed in the vessel lumen. It is think that these cases are important because they are being reported for the first time in Kyrgyzstan.
Características clínicas, macroscópicas, citomorfológicas e histopatológicas del tumor venéreo transmisible canino en dos perras: Primer informe de Kirguistán. Caso clinico
Keywords: Canine transmissible venereal tumor; clinic; cytomorphologic; macroscopic; histopathologic